CT KUB scans for renal colic: Optimisation of scan range to reduce patient radiation burden. Issue 3 (August 2021) - Ghoshal, N.; Gaikstas, G.
Abstract: Introduction: Non-contrast CT KUB scans performed to assess renal colic should be limited to scanning between the upper pole of the highest kidney and the pubic symphysis to minimise unnecessary irradiation. This audit aimed to assess the amount of overscanning in CT KUBs outside this range. Methods: CT KUB scans taken over a 10-day period were assessed. Unnecessary overscan above the highest kidney was measured as a percentage of the total scan range. A target of less than 10% overscanning was set. The vertebral position of the upper pole of the highest kidney was also measured and compared to the actual level of the scan. Results: 88 patients were assessed. 89.8% (79/88) of scans didn't meet the target of less than 10% overscanning above the highest kidney, and were associated with a higher radiation dose to the patient. The average overscanning above the highest pole of the kidney was 16.4% of the whole scan. The average overscan below the pubic symphysis was 1.54%. We also found that 100% of scanned kidneys lied below the upper border of the T11 vertebra, in spite of scans starting as high as T7. Conclusion: A large proportion of scans included unnecessary overscanning above the highest kidney. We have identified the upper border of the T11 vertebral body as a potential location from which to begin the upper margin of a CT KUB scan. Implications for practice: By starting CT KUB scans at the upper border of the T11 vertebral body, we can allow the whole kidney to be imaged while minimising unnecessary overscanning above the kidney, thus lowering excess patient irradiation while still producing high quality scans.